Imidazoline synthesis: mechanistic investigations show that Fe catalysts promote a new multicomponent redox reaction. Issue 19 (28th April 2021) - Coin, Guillaume; Dubourdeaux, Patrick; Bayle, Pierre-Alain; Lebrun, Colette; Maldivi, Pascale; Latour, Jean-Marc
Abstract : Integrated experimental and computational studies reveal a new mechanism for Fe-catalyzed imidazoline synthesis through combined nitrene transfer and acetonitrile attack of a styrenyl radical intermediate. Abstract : Multicomponent reactions are attracting strong interest because they contribute to develop more efficient synthetic chemistry. Understanding their mechanism at the molecular level is thus an important issue to optimize their operation. The development of integrated experimental and theoretical approaches has very recently emerged as most powerful to achieve this goal. In the wake of our recent investigation of amidine synthesis, we used this approach to explore how an Fe-catalyzed aziridination can lead to an imidazoline when run in acetonitrile. We report that the synthesis of imidazoline by combination of styrene, acetonitrile, an iron catalyst and a nitrene precursor occurs along a new kind of multicomponent reaction. The formation of imidazoline results from acetonitrile interception of a benzyl radical styrene aziridination intermediate within Fe coordination sphere, as opposed to classical nucleophilic opening of the aziridine by a Lewis acid. Comparison of this mechanism to that of amidine formation allows a rationalization of the modes of intermediates trapping by acetonitrile according to the oxidation state Fe active species. The molecular understanding of these processes may help to design other multicomponent reactions.